Degradasi Zat Warna Tekstil Remazol Orange 3R Menggunakan Metode Elektrokoagulasi dengan Elektroda Logam Besi - Suseno; Petrus Darmawan; Yari Mukti Wibowo (Jurnal Serambi Engineering, 2026)
Removal of dyes from textile industrial wastewater can be done using microbiological, physical and physicochemical methods. These methods have weaknesses, namely they are less effective, expensive and require further treatment. One alternative method for removing dyes from textile industry wastewater is the electrochemical method, which can be done more quickly, cheaply and effectively. This study aims to determine the effectiveness of electrochemical methods, especially electrocoagulation, in removing dyes, especially Remazol Orange 3R dyes used in the textile industry. The degradation of the textile dye Remazol Orange 3R in this study was carried out using the electrocoagulation method using iron metal electrodes. The equipment used in this study included a plastic vessel, an electric stirrer, and anodes and cathodes made of ferrous metal. The degradation process of the Remazol Orange 3R textile dye was carried out using a batch system with varying stirring or contact times of 15, 30, 45, and 60 minutes. The percentage decrease in absorbance of the dye solution was measured using a UV-Vis spectrophotometer at the maximum wavelength. The results of the study showed that the highest percentage of absorbance reduction, namely 98.36%, was at a contact time of 30 minutes. It can be concluded that the electrocoagulation method with iron electrodes has the potential to be used as a wastewater treatment option, to degrade dyes from textile industry wastewater.